Étude d'impact social et déforestation dans le secteur Turumbu,Territoire d'Isangi,République Démocratique du Congo - Frédéric Esiso Asia Amani,; Désiré Isetcha Tawiti,; Itindi, Jérôme Waliala Apataki; Yuma, Alexis-Toussaint Kawaya; Taylor Athongo Lilembu ,; Joel Bondekwe Baruti ,; Christian Angbilia Mokalo ,; Faustin Likaka Balombo , (IJRDO - Journal of Social Science and Humanities Research, 2019)
The development model based on the industrial exploitation of forests must be abandoned in favor of a pro-poor and specifically pro-Turumbu alternative vision focused on the interests and respect of the cultural values of indigenous communities. Effective mechanisms will therefore need to be put in place to enable a participatory decision-making process in relation to logging, ie a prior informed consent process open to Turumbu people and other forest communities.However, the mode of governance of the State will have to be very decisive to achieve effective and efficient results, especially in the political context of the DR Congo. The discourse of the well-being of every man and of all man must prevail over that of individual selfish interests.